Synchronization in Interpersonal Speech - Amiriparian, Shahin; Han, Jing; Schmitt, Maximilian; Baird, Alice; Mallol-Ragolta, Adria; Milling, Manuel; Gerczuk, Maurice; Schuller, Björn (Frontiers in Robotics and AI, 2019)
During both positive and negative dyadic exchanges, individuals will often unconsciously imitate their partner. A substantial amount of research has been made on this phenomenon and such studies have shown that synchronisation between communication partners can improve interpersonal relationships. Automatic computational approaches for recognising synchrony are still in their infancy. In this study, we extend on previous work in which we applied a novel method utilising hand-crafted low-level acoustic descriptors and autoencoders (AEs) to analyse synchrony in the speech domain. For this purpose, a database consisting of 394 in-the-wild speakers from 6 different cultures, is used. For each speaker in the dyadic exchange, two AEs are implemented. Post the training phase, the acoustic features for one of the speakers is tested using the AE trained on their dyadic partner. In this same way, we also explore the benefits that deep representations from audio may have, implementing the state-of-the-art Deep Spectrum toolkit. For all speakers at varied time-points during their interaction, the calculation of reconstruction error from the AE trained on their respective dyadic partner is made. The results obtained from this acoustic analysis are then compared with the linguistic experiments based on word counts and word embeddings generated by our word2vec approach. The results demonstrate that there is a degree of synchrony during all interactions. We also find that, this degree varies across the 6 cultures found in the investigated database. These findings are further substantiated through the use of 4096 dimensional Deep Spectrum features.